To the uttermost parts of the earth : legal imagination and international power, 1300-1870 - Koskenniemi, Martti (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
"To the Uttermost Parts of the Earth addresses the uses of law by successive generations of lawyers, theologians, philosophers and political writers to deal with the exercises of power beyond the single polity. From the novel understanding of royal authority as analogous to that of a Roman emperor in the 13th century to the treatment of an expanding bourgeois civil society in the early 19th century, the book traces the use of the notions of sovereignty and property across more than five centuries of reflection on the international exercise of European power. The book not only transcends the conventional limits between private and public law, domestic and international law, but shows how such limits were constituted in the first place. Its thesis is that European power is neither the power of state nor that of capital. Instead it has always been and continues to exist as a locally specific, legally constituted combination of the two"--
Legal imagination in a Christian world : ruling France c. 1300 -- The political theology of jus gentium : the expansion of Spain 1524-1559 -- Italian lessons : ius gentium & reason of state -- The rule of law : Grotius -- Governing sovereignty : negotiating French "absolutism" in Europe 1625-1715 -- Reason, revolution, restoration : European public law 1715-1804 -- Colonies, companies, slaves. French dominium in the world 1627-1804 -- The law and economics of state-building : England c. 1450-c. 1650 -- "Giving law to the world" : England c. 1635-c.1830 -- Global law : ruling the British empire -- A science of state-machines. Ius naturae et gentium as a German discipline c. 1500-1758 -- The end of natural law. German freedom, 1734-1821.
Includes bibliographical references (pages : 968- 1069) and index.
Keywords: Grotius, Hugo, -- 1583-1645; International law -- History; Rule of law -- History; Religion and law -- History; Natural law -- History